EVALUATION OF ANTIOXIDANT FUNCTIONALITY OF FISH COLLAGEN ENZYMIC HYDROLYSATE - & Shakir, Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study aimed to investigate the anti- oxidative  function of catfish collagen hydrolysate in beef minced meat samples through 10 days  storage at 4 o C. Collagen hydrolysate were added to minced meat sample  at two different concentrations (50 & 100 mg/100gm) . The experiment consist from control sample (C without additives) , BHT sample ( B  with 200ppm  butylated hydroxytoluene ) , collagenase hydrolysate samples  C.C.H1, C.C.H2 (100&50 mg/100gm minced meat)  respectively, and collagenase-trypsin hydrolysate samples  C.H.T1 & C.H.T2 respectively (50,100mg/100gm minced meat). Peroxide values (PV), thiobarbutyric acid TBA, free fatty acid (FFA) , pH , total volatile nitrogen TVN values and total plate count assay at 0., 3, 7., 10 days  were determined  . PV of the BHT, C.C.H2 , C.H.T2, C.C.H1, C.H.T1 groups  were significantly (p